2007
DOI: 10.1002/ptr.2247
|View full text |Cite
|
Sign up to set email alerts
|

Low concentration of 3‐carene stimulates the differentiation of mouse osteoblastic MC3T3‐E1 subclone 4 cells

Abstract: Recently, natural products have gained more interest as alternative treatments for metabolic bone disorders and for the maintenance of bone health. In this study, the anabolic activities of 89 natural compounds were evaluated by measuring the amount of newly synthesized calcium in the differentiation process of mouse osteoblastic MC3T3-E1 subclone 4 cells. Of these compounds, a low concentration (up to 5 μ μ μ μ μM) of 3-carene, which is a bicyclic monoterpene in essential oils extracted from pine trees, was s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2008
2008
2011
2011

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 22 publications
1
18
0
Order By: Relevance
“…Isolation of total RNA, synthesis of cDNA, and real-time quantitative PCR (QPCR) were carried out as described previously (Jeong et al, 2008). In brief, total RNA was isolated with TRIzol reagent.…”
Section: Evaluation Of Mrna Expression Levelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Isolation of total RNA, synthesis of cDNA, and real-time quantitative PCR (QPCR) were carried out as described previously (Jeong et al, 2008). In brief, total RNA was isolated with TRIzol reagent.…”
Section: Evaluation Of Mrna Expression Levelsmentioning
confidence: 99%
“…Western blot analysis was carried out as described previously (Jeong et al, 2008). After the blotting procedure, the membranes were stained with Ponceau S staining solution to determine the amount of loaded proteins and the efficiency of transfer.…”
Section: Western Blot Analysismentioning
confidence: 99%
“…In our study the abundance of 3-carene was the highest. It has various medicinal uses (Jeong et al, 2007;Lastbom et al, 1998). On the other hand, M. paniculata contained abundance of caryophyllene oxide which has antifungal activities (Yang et al, 1999).…”
Section: --mentioning
confidence: 99%
“…Cis-verbenol, a metabolite of a-pinene occurring in human urine, inhibited osteoclastic resorption activity [Eriksson and Levin, 1996]. 3-Carene, a bicyclic monoterpene occurring in pine trees has been found to stimulate the mineralization in osteoblastic cells and its activity could result from its potential to promote the activation of mitogen-activated protein (MAP) kinases signaling pathways and the transcript levels of osteoblast mineralization-related genes such as osteopontin and type I collagen [Jeong et al, 2008]. It has been suggested that monoterpenes act directly on bone cells, not via the stimulation of calciotropic hormones, and the mode of action is thought to be via inhibition of the mevalonate pathway and the prenylation of small G proteins such as Ras, Rho, and Rac [Clegg et al, 1982;Crowell et al, 1991;Ren et al, 1997].…”
mentioning
confidence: 99%